2004
DOI: 10.1093/humrep/deh154
|View full text |Cite
|
Sign up to set email alerts
|

Recovery, survival and functional evaluation by transplantation of frozen-thawed mouse germ cells

Abstract: Reinitiation of spermatogenesis is possible after cryopreservation of testicular germ cell suspensions. Although cell survival was acceptable, our results after TGCT show that our protocols need further improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(76 citation statements)
references
References 27 publications
5
61
1
9
Order By: Relevance
“…A study in rats already highlighted the differential sensitivity of immature tissue to the selection of the cryoprotectants and their concentrations (Unni et al, 2011). Furthermore, functional integrity evaluation of cryopreserved tissue is fundamental to validate a freezing -thawing/cooling -warming procedure, since previous studies concluded that a high survival rate of morphologically normal SG does not necessarily imply that those SG are actually functional (Frederickx et al, 2004;Jahnukainen et al, 2007;Zeng et al 2009). The opposite may also be true; our previous study showed that cryoinjured tissue retained its function and could recover after transplantation (Baert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A study in rats already highlighted the differential sensitivity of immature tissue to the selection of the cryoprotectants and their concentrations (Unni et al, 2011). Furthermore, functional integrity evaluation of cryopreserved tissue is fundamental to validate a freezing -thawing/cooling -warming procedure, since previous studies concluded that a high survival rate of morphologically normal SG does not necessarily imply that those SG are actually functional (Frederickx et al, 2004;Jahnukainen et al, 2007;Zeng et al 2009). The opposite may also be true; our previous study showed that cryoinjured tissue retained its function and could recover after transplantation (Baert et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…62 In this study, the cryopreservation method of Izadyar et al 43 was used to isolate neonate testicular cells as well as to fragment seminiferous tubules. Goossens et al 63 cryopreserved mouse tissue pieces in ethylene glycol and DMSO as cryoprotectant while their protocols had already been used for freezing testicular stem cell suspensions by Frederickx et al 64 They obtained the best morphology of the basal compartment when the cryoprotective medium contained DMSO. 63 Honaramooz et al 65 investigated the effects of cooling or cryopreservation with DMSO on the testis fragments of pigs before grafting and observed complete spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that a number of stresses during slow freezing, including osmotic stress and, stress to cell-junction and cell-transport systems (63,64), can contribute to the loss of pluripotency. Using straws as a container, programmed cell freezer and/or a high concentration of FBS/KO-SR, the survival rate of hESCs after slow-freezing and thawing was found to increase nearly 80%, with no apparent increase in differentiation (65,66).…”
Section: Cryopreservation Conditions For Human Embryonic Stem Cellsmentioning
confidence: 99%